Economic Evaluation of Rehabilitation of Spinal Cord Injury Patients in Iran in 2019 - Mirtaher Mousavi; Rajabali Daroudi; Marzieh Shirazikhah; Mehdi Alizadeh Zarei; Hamidreza Hendi; Faezeh Joghataei; Ali Darvishi (Journal of Rehabilitation, 2022)
Objective Despite the evidence that rehabilitation interventions are effective for spinal cord injury (SCI) patients, these interventions usually impose costs on the health system. Therefore, it is necessary to examine the cost-effectiveness of these interventions for the health system of countries through economic evaluation. In this study, we examined the cost-effectiveness and net financial benefits of rehabilitation services in treating spinal cord injuries in Iran. Materials & Methods Considering that this research is the first economic evaluation study related to spinal cord injury rehabilitation, the first stage of the economic evaluation was dedicated to designing an economic evaluation model. The model was designed based on disease groups, the natural course of the disease, the details of rehabilitation interventions for spinal cord injury patients in different disease groups, clinical outcomes, probability of occurrence of outcomes, and related costs. The structure of the economic evaluation model of this study is based on the design of a lifetime Markov model with a 1-year cycle length for each strategy and two groups of patients (paraplegia and tetraplegia). In this study, we also used the incremental cost-effectiveness ratio (ICER) to determine the cost of the most effective strategy. All findings were analyzed using Excel 2016 and TreeAge 2011 software. Results According to the annual incidence of spinal cord injury patients in need of rehabilitation services in the country, which is about 2000 people, based on public sector tariffs, the total annual cost of SCI rehabilitation in Iran in the paraplegia group ranges from 32997 to 40200 million Iranian Rials (IRR) and in the tetraplegia group from 25476 to 26119 million IRR in mild to very severe conditions. Also, the total rehabilitation costs of SCI patients based on public sector tariffs in one year were calculated to equal 256847 million IRR. Similarly, based on private sector tariffs, the total annual costs of SCI rehabilitation in the paraplegia group were estimated from 86374 to 103122 million IRR and in the tetraplegia group from 67509 to 68997 million IRR in mild to very severe cases. Meanwhile, the total rehabilitation costs of SCI patients were calculated based on private sector tariffs in one year, equivalent to 668847 million IRR. Also, the average lifetime of SCI patients undergoing rehabilitation is lower compared to non-rehabilitation and also has higher QALY (The quality-adjusted life year) values, which indicates the dominance of the rehabilitation strategy. The amount of ICER, in this case, is estimated based on public sector tariffs equal to negative 674 million IRR and based on private sector tariffs equal to negative 629 million IRR per QALY unit. Possible sensitivity analysis of the results and Monte Carlo simulation in both scenarios confirmed the initial analysis findings with high probability. Based on the public sector tariff, the net amount of incremental financial benefits of rehabilitation for the total annual incidence is estimated at 8991 billion IRR. These amounts were calculated based on private sector tariffs of 8579 billion IRR. Conclusion Generally, the results of this economic evaluation showed that the rehabilitation of spinal cord injury patients in Iran, based on public and private sector tariffs, is quite cost-effective and has significant net positive financial benefits. The results of the sensitivity analysis also confirmed this finding.